VP191 Peripheral Nerve Field Stimulation For Chronic Low Back Pain. (2017) - Rhainds, Marc; Larocque, Brigitte; Bussières, Sylvain; Nourrisat, Alice; Coulombe, Martin; Cantin, Léo; Canuel, Jean-Francois; Prudhomme, Michel
Abstract : INTRODUCTION: Despite numerous medical, pharmacological and surgical approaches for chronic low back pain (LBP), many patients continue to complain of severe disabling pain. Peripheral nerve field stimulation (PNfS), alone or combined with spinal cord stimulation, is a neuromodulation procedure that have been recently developed and implemented in our hospital. We conducted a Health Technology Assessment (HTA) to determine if PNfS may be considered as a standard of practice in the management of intractable LBP and failed back surgery syndrome (FBSS). METHODS: An interdisciplinary group of experts was involved in the project. A systematic review (SR) was performed in several databases and grey literature to identify clinical practice guidelines, SR and observational studies published through September 2016. A survey was conducted among other chronic pain centers in Canada to document PNfS use in LBP and FBSS treatment. RESULTS: Data on effectiveness and safety of PNfS in chronic LBP treatment were scarce. Short-term results (3-12 months) from small sample and low quality studies suggest that PNfS, alone or combined with spinal cord stimulation, is associated with pain intensity and opioid use reductions. Effects on functional status and quality of life remain undetermined. Most frequent adverse events reported with PNfS devices are lead migrations, discomfort or pain and surgical site infections. No other Canadian pain centers were found to use PNfS in chronic LBP or FBSS. CONCLUSIONS: PNfS is potentially a beneficial treatment option for patients with chronic low back pain or FBSS. However, the value of this innovative treatment remains unknown. Among factors to be clarified are target population (any chronic low back pain or FBSS), use of PNfS alone or combined with spinal cord stimulation, long-term effects, and comparison with conventional medical management. PNfS use in chronic LBP has to be assessed through a rigorous framework before its introduction as a standard medical practice.